2014
DOI: 10.15446/caldasia.v36n1.43894
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic Analysis Whithin the Pristimantis Unistrigatus (Anura, Craugastoridae) Group Based on Morphological Characters

Abstract: We present a phylogenetic analysis within the Pristimantis unistrigatus group (Anura, Craugastoridae) of Colombia. Characters from the superficial muscles of the hands and feet as well as external characters were taken for analysis. Most of the muscle characters were observed directly, and some were taken from the literature. Similarly, the external ones were taken mostly from the original descriptions and others from the literature as well. Two matrices were constructed, as the species belonging to this group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
13

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(39 citation statements)
references
References 22 publications
0
26
0
13
Order By: Relevance
“…Based on their geographic location and morphological affinities, it is clear that the species described herein reside within the genus Pristimantis, subgenus Pristimantis, as defined by Hedges et al (2008). It is not possible to ascertain their close phylogenetic relationships without a more comprehensive analysis, and we refer them to species groups with the understanding that the P. unistrigatus species group is most likely not monophyletic (Hedges et al 2008;Hoyos et al 2014). To coin appropriate common names for these species, we follow the Table 1.…”
Section: Descriptionsmentioning
confidence: 99%
“…Based on their geographic location and morphological affinities, it is clear that the species described herein reside within the genus Pristimantis, subgenus Pristimantis, as defined by Hedges et al (2008). It is not possible to ascertain their close phylogenetic relationships without a more comprehensive analysis, and we refer them to species groups with the understanding that the P. unistrigatus species group is most likely not monophyletic (Hedges et al 2008;Hoyos et al 2014). To coin appropriate common names for these species, we follow the Table 1.…”
Section: Descriptionsmentioning
confidence: 99%
“…In the new millennium, Burton (2001) studied the foot musculature of Limnodynastidae and Myobatrachidae, Faivovich (2002) defined a few characters of the foot musculature in a study of Scinax (Hylidae), and Burton (2004) carried out a detailed study of the foot musculature of a taxonomically dense sample of Hylidae (at that time including Hemiphractidae) and several outgroup clades. More recently, Salgar et al (2009) reported on the foot musculature of a single species of Pristimantis (Craugastoridae), while Hoyos et al (2014) defined characters of foot musculature in a quantitative phylogenetic analysis of one species group of Pristimantis and Hoyos & Salgar (2016) focused on variation in one species of Dendropsophus (Hylidae). These few studies have revealed an enticing glimpse into the variation of these muscles across taxonomic groups, but many more clades must be studied in order to understand their evolutionary history and elucidate the functional and behavioral significance of the morphological differences.…”
Section: Introductionmentioning
confidence: 99%
“…Flexor digitorum communis Same (Ecker, 1864;Abdala and Diogo, 2010;Diogo and Abdala, 2010;Diogo and Ziermann, 2014;Diogo et al, 2018;Fratani et al, 2018Fratani et al, , 2020Soliz et al, 2020); épitrochlosous-phalangettien (Dugès, 1834); palmaris longus (Gaupp, 1895(Gaupp, , 1896Kändler, 1924;Liem, 1970Liem, , 1973Liem and Hosmer, 1973;Davies and Burton, 1982;Burton, 1983;Oka et al, 1984;Duellman and Trueb, 1986;Burton, 1996Burton, , 1998aFaivovich, 2002;Faivovich et al, 2005;Manzano et al, 2008;Salgar et al, 2009;Hoyos et al, 2014;Hoyos and Salgar, 2016); flexor primordialis communis (Ribbing, 1907(Ribbing, : part. a , 1911 ); flexor digitorum communis longus (Manzano et al, 2008;Oliveira-Lagôa et al, 2019); flexor digitorum longus (Abdala et al, 2018;Oliveira-Lagôa et al, 2019) Flexor accessorius…”
Section: Ventral Forearmmentioning
confidence: 99%
“…Manzano et al (2008) studied characters related to specializations for grasping in the forelimb of two hylids. Salgar et al (2009) reported on the foot musculature of a species of Pristimantis (Craugastoridae), whereas Hoyos et al (2014) defined characters of foot musculature in a quantitative phylogenetic analysis of the Pristimantis unistrigatus species group, and Hoyos and Salgar (2016) focused on variation within Dendropsophus luddeckei (as D. labialis; Hylidae). Diogo and Ziermann (2014) studied the development of the fore-and hind-limb muscles using Eleutherodactylus coqui (Eleutherodactylidae) as a model.…”
Section: Introductionmentioning
confidence: 99%